Effect of precursors on the growth and physiochemical properties of bio-mimetic ZnFe2 O4 nanocomposites for photoelectrochemical application - Mohd Faizal Md Nasir; Wan Ramli Wan Daud; Mohamad Azuwa Mohamed; Mohamad Hafiz Mamat; Saifollah Abdullah; Mohamad Rusop Mahmood (Penerbit Universiti Kebangsaan Malaysia, 2020)
Zinc ferrite (ZnFe2 O4 ) photocatalysts have been prepared with different types of zinc precursors using the bio-mimetic synthesis method. The kapok fibre (Ceiba pentandra (L.) Gaertn) used as a sacrificial template. The physiochemical of prepared bio-mimetic materials were carried out thoroughly in this work. The FESEM analysis in mimetic zinc ferrite catalysts shows a distinctly different structural transition under different precursors conditions. The acetate precursor formed a hollow tubular structure while other precursors formed a hierarchal fibril structure. X-ray diffraction analysis showed a distinctly different phase transition while UV-Vis spectroscopy recorded variable optical properties beneath different precursor conditions. The EDX and ATR-FTIR spectroscopy confirmed the formation of the pure composite after the annealing process. Different type of precursors that used have leads to tuneable of the magnetic properties of the prepared materials. Electrophoretic deposition (EPD) method has been used to fabricate the synthesized materials as photo-electrodes on the FTO substrate then evaluated for photoelectrochemical (PEC) application. Changing the precursors in the preparation method show a significant effect on physicochemical and PEC performance. The morphology and surface structure of the prepared catalysts are correlated with the alteration of the precursors, then attributed to the charge transfer properties of the photocurrent density in PEC system. The bio-templated zinc ferrite catalysts are promising photoanode in the photocatalytic activities. It is interesting to note that the various forms of multi-structure such as hollow fibril core-shell offers an enormous impact in designing active photocatalyst with superior performance.